2018
DOI: 10.3389/fnagi.2018.00101
|View full text |Cite
|
Sign up to set email alerts
|

Theta-Gamma Coupling and Working Memory in Alzheimer’s Dementia and Mild Cognitive Impairment

Abstract: Working memory deficits are common among individuals with Alzheimer’s dementia (AD) or mild cognitive impairment (MCI). Yet, little is known about the mechanisms underlying these deficits. Theta-gamma coupling—the modulation of high-frequency gamma oscillations by low-frequency theta oscillations—is a neurophysiologic process underlying working memory. We assessed the relationship between theta-gamma coupling and working memory deficits in AD and MCI. We hypothesized that: (1) individuals with AD would display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 52 publications
7
125
1
1
Order By: Relevance
“…Herein we examine the effect of VFX on this endpoint. In addition, since increased gamma power has been linked to enhanced working memory (Alekseichuk et al, 2016;Goodman et al, 2018;Martorell et al, 2019, Iaccarino et al, 2016, we also examine the effect of CORT and VFX on spontaneous alternations in the T maze, which has been shown to measure spatial working memory in mice (Shoji et al, 2012).…”
Section: Increased Anxiety and Reduced Working Memory In Cort-treatedmentioning
confidence: 99%
“…Herein we examine the effect of VFX on this endpoint. In addition, since increased gamma power has been linked to enhanced working memory (Alekseichuk et al, 2016;Goodman et al, 2018;Martorell et al, 2019, Iaccarino et al, 2016, we also examine the effect of CORT and VFX on spontaneous alternations in the T maze, which has been shown to measure spatial working memory in mice (Shoji et al, 2012).…”
Section: Increased Anxiety and Reduced Working Memory In Cort-treatedmentioning
confidence: 99%
“…Indeed, several human EEG studies have demonstrated a correlation between the modulation of gamma amplitude by theta phase in the frontal cortices and working memory processes (Canolty and Knight, 2010;Lisman and Jensen, 2013;Rajji et al, 2017). Weakening in this cross-frequency interaction has been correlated with the severity of cognitive impairment and dementia in patients (Goodman et al, 2018). Here we found that the phase-amplitude modulation between theta (4-8Hz) and low gamma (30-60Hz) from different recording sites in the dlPFC increased during the session (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in humans with AD, an enhanced CFC between the gamma and low-frequency bands (in particular, theta) compared to healthy control was revealed [141]. During performance of working memory tasks, evidence for a relationship between altered theta-gamma coupling and working memory deficits in individuals with AD was obtained [143].…”
Section: A L T E R a T I O N S I N T H E T A -G A M M A C O H E R E Nmentioning
confidence: 95%